Milankovitch, the father of paleoclimate modeling - A. Berger (Climate of the Past, 2021)
The history of the long-term variations in the astronomical elements used in paleoclimate research shows that, contrary to what might be thought, Milutin Milankovitch is not the father of the astronomical theory but he is definitely the father of paleoclimate modeling. He did not calculate these long-term variations himself but used them extensively for calculating the “secular march” of incoming solar radiation. He advanced our understanding of Quaternary climate variations by two important and original contributions fully described in his Canon of insolation. These are the definition and use of caloric seasons and the concept of the “mathematical climate”. How his mathematical model allowed him to give the caloric summer and winter insolation a climatological meaning is illustrated.